A study of particulate matter (PM10) and it effects on lung function performance among petrol pump workers / Farhanim Alias - Alias, Farhanim (2010)
This study determines the association between lung function Performance and exposures to particulate matter (PMio) among petrol pump workers working close to two dominant highways connected within Klang Valley which is the Federal Highway and Damansara-Puchong Highway (LDP). Twelve petrol pumps stations with a total of sixty two petrol pump workers were involved in this study. Thirty one workers working outdoors (filling attendants) formed the study population, while another thirty one workers working indoors (cashiers) served as control. Twelve of them carried a PMio personal monitoring during their 8 hour working day using personal air sampling pump model GilAir 5 with the Polyvinyl Chloride (PVC) filters. The respirable particle concentration was determined using the gravimetric method. The lung function Performances were assessed using model Vitolograph 2120 to obtain three main lung function Performances namely Force Vital Capacity (FVC%), Force Expiratory Volume at one second (FEV1%) and ratio of FEV1 over FVC. Personal PMio concentration was higher in the study group (mean=1.845±0.677) compared to control groups (mean=0.96±0.033). Spearman correlation test showed that particulate matter concentration had a significant effect on lung function Performances for both groups. The FEV1 % and FEV 1/FVC % were decreased in the study group (mean^76.21± 19.51) with the significant different (p<0.05) for both tests. The lung function Performance also showed significant correlation with the working years of petrol pump workers (r= -0.369). The study populations had significantly more sore throat and short breath than the control (p<0.05). Other respiratory Symptoms such as eye irritation, running nose, dryness of mucous and cough are more dominant among the study population. The occupational exposure of petrol pumps workers does not exceed any currently applicable occupational exposure limit. Although the personal PMio concentration exposure among study population was far below legal limits, there is an evidence of decrement on lung function Performances experienced by the petrol pump workers.